1988
DOI: 10.1136/hrt.60.5.390
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, hyperinsulinaemia, and coronary risk factors in Bangladeshis in east London.

Abstract: Immigrants from the Indian subcontinent (South Asians) in England and Wales have higher morbidity and mortality from coronary heart disease than the general population; this seems to apply to both Hindus and Muslims. Studies in north west London and Trinidad found that the increased risk of coronary heart disease in Indians was not explained by dietary fat intakes, smoking, blood pressure, or plasma lipids. In the present study the distribution of coronary risk factors was measured in an East London borough wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
5
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(154 citation statements)
references
References 22 publications
7
139
5
3
Order By: Relevance
“…Participants were sampled from general practitioner registers or health centres and community hospital registries. 12,[14][15][16][17][18] Two studies used samples from a population or community register. 20,21 One study used samples from areas as identified by the postcode directory.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants were sampled from general practitioner registers or health centres and community hospital registries. 12,[14][15][16][17][18] Two studies used samples from a population or community register. 20,21 One study used samples from areas as identified by the postcode directory.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
“…17,18 Three studies reported on multiple South Asian subgroups (Indian, Pakistani, Bangladeshi) separately, 18,22,23 others reported only one subgroup or a combined South Asian population. [14][15][16][17]19,20,26 Most studies used Hawksley random zero sphygmomanometers to measure BP, 15,16,19 whereas two studies used mercury, 18,21 or automated devices such as the Omron (OMRON, Omron Matsusaka Co. Ltd, Kyoto, Japan), Dinamap 8100 (GE Healthcare, Critikon, FL, USA) and Roche (F Hoffmann-La Roche Ltd., Basel, Switzerland) sphygmomanometers. 12,17,20,23 Subjects were seated and quiet for at least 5 min before BP measurement.…”
Section: Overview Of Methods Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations